Bioprospecção de fungos filamentosos (Ascomycetes) isolados de sedimento de mangue para produção do complexo enzimático celulolítico utilizando resíduos agroindustriais com substratos. - Mororó, Maria Cleudenôra Cássia (2017)
Cellulases (E.C. 3.2.1.4) are enzymes responsible for the degradation of cellulose, are molecules capable of accelerating chemical reactions and breaking the chemical bonds between glucose units. Cellulases correspond to the complex consisting of three enzymes endoglucanases, exoglucanases and beta-glucosidases, with diverse applications, being the microbial biotechnological processes responsible for a great part of the world economy, yet the costs of production are still very high. In this context, 25 strains of filamentous fungi (Ascomycetes) isolated from mangrove sediments of Rio Formoso, PE, Brazil, were investigated to investigate the production potential of the enzymes of the cellulolytic complex. The initial studies were carried out by selecting the fungi with the highest enzymatic activity, through the detection of cellulolytic activity in solid synthetic medium, with carboxymethylcellulose (CMC) as the substrate. The results indicated the presence of the cellulase enzyme through the formation of halo in 3 strains of the genus Trichoderma, 3 strains of the genus Aspergillus and 1 strain of the genus Penicillium. The most representative enzymatic indices were those of Penicillium sp. UCP 0279 with Index of 2,2, followed by Aspergillus flavus UCP 1413 with enzymatic index of 1,7. Submerged fermentations were carried out to evaluate the endoglucanase activity, exoglucanase and β-glycosidase, using agroindustrial residues, tangerine peel, pineapple peel, pineapple crown, wheat bran and corn bran as substrate. The results indicated a CMCase activity of 20.2 IU / mL for Penicillium sp. UCP 0279, with wheat bran as substrate in 72 h of fermentation and an activity of 18.3 IU / mL in 24 h with the pineapple crown. For the Aspergillus flavus UCP 1413, the yield was 14.9 IU / mL and 14.5 IU / mL with the residues of corn bran and pineapple peel respectively, and both results were obtained with 24 h of fermentation. The FPase activity for Penicillium sp. UCP 0279, using pineapple peel as substrate had 45.5 IU / mL and the tangerine peel 42.8 IU / mL, both in fermentation at 48 h. For A. flavus UCP 1413 the pineapple crown presented 25.0 IU / mL enzymatic activity in 24 h and the pineapple peel 14.4 U / mL at the same time. In the activity of the enzyme β-glycosidase, Penicillium sp. UCP 0279 showed a production of 18.2 IU / mL in 24 h, with the pineapple crown residue and the pineapple peel had 9.1 IU / mL in 48 h. The A. flavus UCP 1413 presented with 96 h of fermentation an activity of 16.9 U / mL and 14.5 U / mL, with wheat bran and corn bran, respectively.